The Hippo Pathway in Innate Anti-microbial Immunity and Anti-tumor Immunity - Zhang, Qian; Zhou, Ruyuan; Xu, Pinglong (Frontiers in Immunology, 2020)
The Hippo pathway responds to diverse environmental cues and plays key roles in cell fate determination, tissue homeostasis, and organ regeneration. Aberrant Hippo signaling, on the other hand, has frequently been implicated in diversified pathologies such as cancer and immune dysfunction. Here, we summarize the recent but rapid progress in understanding the involvement of the Hippo pathway in innate immunity, with a special focus on the intrinsic mechanisms and mutual interactions between Hippo-YAP signaling and the innate immune response and its physiological impacts on anti-microbial immunity and anti-tumor immunity. Moving forward, we believe that systematic investigations under the physiological setting are needed to draw a clearer picture of the actions of Hippo in innate immunity.